Bioequivalency of Two Piroxicam Products in Plasma by High Performance Liquid Chromatography - Dhia M. Sheet Al-Shakargi, Shaimaa (Tikrit Journal of Pharmaceutical Sciences, 2023)
To determine piroxicam in human plasma and to compare the pharmacokinetic profile of the test drug (Piroxicam Tablet) and the reference drug (Piroxicam Capsule) for bioequivalence study. This study represents the result of a randomized, single dose, two period crossover studies in 15 healthy volunteers to assess the bioequivalence of two formulations of piroxicam 20 mg. The blood samples (5 ml) were drawn concomitantly from 1-72 hours after oral administration of a single dose of 20 mg piroxicam capsules (Piroxisam)® (Samarra Drug Industry) as reference drug to 15 volunteers then after 15 days wash out period, the same volunteers were given 20 mg of piroxisam tablets (Samarra Drug Industry) as test drug. The pharmacokinetic parameters were obtained from the mean plasma concentration measured at various sampling times. Cmax and Tmax of both products were similar. Ka and Kelm values of were very close between test and reference formulations. The AUC value of piroxicam tablet was lower than that of capsule. The test formulation was found to be bioequivalent to reference formulation based on the pharmacokinetic parameters